2000
DOI: 10.1046/j.1365-2982.2000.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of intestinal motor responses to various stimuli after Nippostrongylus brasiliensis infection in rats: role of mast cells

Abstract: Nippostrongylus brasiliensis infection induces jejunal mastocytosis associated with enteric nerve remodelling in rats. The aim of this study was to evaluate the intestinal motility responses to meals and to neurotransmitters involved in the control of gut motility (acetylcholine (carbachol), substance P and neurokinin A) in both control and N. brasiliensis-infected rats 30 days post-infection. All rats were equipped with NiCr electrodes in the jejunum to record myoelectrical activity. The duration of disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
2
17
1
1
Order By: Relevance
“…In contrast to a T. spiralis infection in which macrophages are the dominant immune cell in the musculature, mast cells penetrated the musculature after a N. brasiliensis infection 45 and changes in motor function in response to a N. brasiliensis infection depended on the presence of mast cells. 46 Interestingly, the presence of mast cells in the musculature was long lasting with a half life of 40 days, which may explain the severity of the damage to ICC. 45 The present study provides further evidence for the T. Spiralis-infected mouse being a model for postinfectious enteropathies, a significant problem in clinical gastroenterology.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a T. spiralis infection in which macrophages are the dominant immune cell in the musculature, mast cells penetrated the musculature after a N. brasiliensis infection 45 and changes in motor function in response to a N. brasiliensis infection depended on the presence of mast cells. 46 Interestingly, the presence of mast cells in the musculature was long lasting with a half life of 40 days, which may explain the severity of the damage to ICC. 45 The present study provides further evidence for the T. Spiralis-infected mouse being a model for postinfectious enteropathies, a significant problem in clinical gastroenterology.…”
Section: Discussionmentioning
confidence: 99%
“…In the small bowel, this inhibition is mediated by histamine, 5-HT and prostaglandins and leukotrienes, whereas in the colon inhibition is mediated mainly by 5-HT3 receptors, substance P and vagal afferents [120]. In the parasite model, in the post-infection phase, an enhanced motor response to carbachol and neurokinin A develops and this response is also mast celldependent [121].…”
Section: Mast Cells and Intestinal Motilitymentioning
confidence: 98%
“…Several studies correlate mast cell activity with the development of functional disorders such as alteration of intestinal permeability (Santos et al, 2001), motor disorders (Gay et al, 2000a), and visceral hypersensitivity (Kreis et al, 1998). We previously demonstrated that activation of mast cells could modify intestinal motility, even in the absence of apparent intestinal inflammation (Saavedra and Vergara, 2005).…”
Section: Discussionmentioning
confidence: 99%